A zinc-based metal–organic framework with a triazine moiety: effective detection of antibiotics and photodegradation dyes in aqueous solution. Issue 13 (13th March 2023) - Chen, Xueyi; Tan, Geng; Chen, Wanyu; Chang, Jiaming; Yue, Yuanmeng; Li, Yameng; Weng, Ng Seik; Zhang, Lilei; Feng, Xun
Abstract : Effective detection of antibiotics and photodegradation using a novel zinc-based metal–organic framework. Abstract : A zinc-based metal–organic framework was constructed by a solvothermal synthesis approach with the formula {[Zn3 (ttta)2 (H2 O)4 ]} n (1 –Zn ) (where H3 ttta = 4, 4′, 4′′-(1, 3, 5-triazine-2, 4, 6-triazinediyl) triazinic acid) and was successfully characterized. In terms of photocatalytic degradation, complex 1 –Zn has a smaller energy band gap and higher degradation efficiency compared to many other Zn-MOFs, and it has good stability and recyclability. Fluorescence detection experiments showed that complex 1 –Zn showed significant specificity in recognition of quinolone antibiotics compared to other antibiotics and showed a better fluorescence quenching rate of metronidazole (MDZ) and tetracycline hydrochloride (TCH). The photodegradation mechanism was investigated by ultraviolet-visible diffuse reflectance spectroscopy (UV-vis DRS) and valence band X-ray photoelectron spectroscopy (VB-XPS). A reasonable mechanism of the fluorescent probe and photodegradation of 1 –Zn was determined by density functional theory calculations.